THU0262 Changes in sonoelastographic characteristics in sjÖgren's syndrome – a five-year follow up. (15th June 2017) - Hofauer, B; Bas, M; Mansour, N; Knopf, A
Abstract : Background: The role of sonography in the evaluation of salivary gland alterations in patients with suspected Sjögren's Syndrome (SS) and its benefit with regard to the diagnosis is part of continuing investigation. Studies on sonoelastographic alterations in the salivary glands of patients with SS have been published during the last years and were able to prove significant differences compared to patients with sicca-symptoms without fulfilling the AECG classification criteria [1, 2]. The available knowledge on longitudinal changes in sonoelastographic characteristics is still limited. Objectives: Which variations of sonoelastographic salivary gland alterations can be observed during the five-year follow up of patients with primary Sjögren's Syndrome? Methods: Patients with primary Sjögren's Syndrome (pSS) diagnosed according to the AECG classification criteria were included in this study. The EULAR SS Patient Reported Index (ESSPRI) was applied for the evaluation of patient's symptoms and the EULAR SS Disease Activity Index (ESSDAI) for systemic features. During 2011 and 2016 the sonoelastographic alterations of the salivary glands in patients with primary Sjögren's Syndrome were evaluated. Acoustic Radiation Force Impulse (ARFI) imaging (=shear wave velocity), Real Time Tissue Elastography (RTTE) and Virtual Touch Tissue Imaging (VTTI) were applied for the sonoelastographic evaluation in addition to B-Mode sonography (BMUS). Results of BMUS, RTTE and VTTI were graded with appropriate scoring systems. Results: Fifty patients diagnosed with pSS were included (45 female, age: 56 years SD =16). In 2011 the mean ESSPRI score was 8.3 (SD =4.6) and the mean ESSDAI score was 5.6 (SD =7.5). Initially, the mean ARFI value of parotid glands was 2.99m/s (SD =0.93) and the mean ARFI value of the submandibular glands was 2.15m/s (SD =0.57). Clinical examination and sonoelastographic evaluation was repeated after five years in 2016, revealing a mean ESSPRI score of 6.1 (SD =3.2, p=0.002) and a mean ESSDAI score of 4.6 (SD =7.0, p<0.001). After five years a significant decline of ARFI values could be observed in the parotid gland (2.33m/s, SD =0.70, p<0.001) while no significant changes of the ARFI of the submandibular gland could be observed. Results of RTTE and VTTI did not change significantly. The mean time interval between onset of first symptoms and first sonographic examination in 2011 was 57.3 months (SD =60.8). Conclusions: The five-year sonoelastographic follow up of salivary gland alterations in patients with pSS revealed a decline in the severity of sonoelastographic alterations of the parotid gland in ARFI imaging, indicating a certain capability for modulation of salivary gland affection in pSS. References: Hofauer B et al. Sonoelastographic Modalities in the Evaluation of Salivary Gland Characteristics in Sjögren's Syndrome. Ultrasound Med Biol 2016; 2) Knopf A et al. Diagnostic utility of Acoustic Radiation Force Impulse (ARFI) imaging in primary Sjoegren's syndrome. Eur Radiol 2015. Disclosure of Interest: None declared